1987
DOI: 10.1063/1.97738
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency excess noise in Nb-Al2O3-Nb Josephson tunnel junctions

Abstract: A fabrication technique for Nb-Al2O3-Nb Josephson tunnel junctions is described that is an alternative to the trilayer method generally used. At 4.2 K the magnitude of the low-frequency noise in the critical current I0 of four junctions with areas 𝒜 ranging from 7.8 to 115 μm2 was characterized by S1/2I0𝒜1/2/I0 =(14±6)pA μm/μA Hz1/2, where SI0 is the spectral density of the excess noise at 1 Hz. The noise power spectrum of one 3×3 μm2 junction exhibited a Lorentzian feature associated with the emptying and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…Taking the contribution from critical-current noise to be 5%, we find S I 0 1 Hz 0:05S 1 Hz=L 2 1:4 10 ÿ12 I 2 0 =Hz for our 2 m 2 area junction. This value is compatible with previous experiments [7], giving a critical-current noise at 20 mK that is a factor of 36 lower than predicted for 4.2 K [12].…”
supporting
confidence: 93%
“…Taking the contribution from critical-current noise to be 5%, we find S I 0 1 Hz 0:05S 1 Hz=L 2 1:4 10 ÿ12 I 2 0 =Hz for our 2 m 2 area junction. This value is compatible with previous experiments [7], giving a critical-current noise at 20 mK that is a factor of 36 lower than predicted for 4.2 K [12].…”
supporting
confidence: 93%
“…junctions with low subgap leakage currents will have low Vf noise. Figure 11 shows an example of a Nb-AI203-Nb junction with a single trap [41]. The junction was resistively shunted and voltage biased at typically 1.5 I1V; the noise currents were measured with a SQUID.…”
Section: /Fnoise In DC Squidsmentioning
confidence: 99%
“…1/f noise in the critical current of Josephson junctions has been observed experimentally [41,42,43,44]. The microscopic source of this noise is unknown, though it has been suggested that the tunneling of atoms or ions is involved [16].…”
Section: −1mentioning
confidence: 99%